Functional basic reading skills in Williams syndrome. Issue 5 (4th July 2018) - Brawn, Gabrielle; Kohnen, Saskia; Tassabehji, May; Porter, Melanie
ABSTRACT: This study investigated whether individuals with Williams syndrome (WS) can attain a functional level of basic reading skills. The Study also investigated broader cognitive factors associated with reading ability in individuals with WS. Thirty individuals with WS participated in this study (mean chronological age 21 years and mean mental age 7 years 7 months). The results supported our hypotheses that: firstly, reading abilities would be heterogeneous in WS; secondly, at least some WS individuals are capable of achieving a functional basic reading level; and thirdly, on average, WS individuals would find reading of nonwords more difficult than reading of regular and irregular words. Moreover, higher reading ability was found to be associated with increased outcomes in adaptive functioning, in particular, Written and Expressive Communication skills and Community Living skills, highlighting the potential benefits of developing reading abilities in WS. Although Intelligence Quotient (IQ) was related to overall basic reading ability generally, it was not found to be a determining factor in reading subtypes. Several cognitive skills known to be related to reading ability in typically developing individuals were found to be associated with reading performance and reading subtypes. Implications for appropriate reading instruction are discussed.